Análisis del uso de las redes sociales y el derecho a la privacidad en los niños, niñas y adolescentes - Álava Bravo, Brianna Vilma (2025)
The objective of this research project is to analyze the use of social networks and their impact on the right to privacy of children and adolescents in Guayaquil. The aim is to understand how the growing use of digital platforms influences the exposure of personal data and how this affects the privacy of minors, considering factors such as the lack of knowledge about digital security and the influence of social networks on their social and emotional development. To achieve this objective, a mixed methodological approach will be used. Techniques will be applied such as interviews with legal experts, and surveys of parents, as well as a documentary analysis of the current regulations on data protection in Ecuador. This approach will allow for a comprehensive understanding of the problem, identifying patterns of social media use and evaluating the level of knowledge and awareness of young people's digital privacy. With the results of this research, it will be possible to propose educational strategies and public policy recommendations that promote responsible use of social networks, with a focus on child protection in digital environments. In addition, efforts will be made to strengthen Internet security through the development of a parental monitoring and control system for local area networks, based on the analysis of the main threats that minors face when interacting on the Internet.